2003
DOI: 10.1007/10849171_81
|View full text |Cite
|
Sign up to set email alerts
|

SDSS-RASS: Next Generation of Cluster-Finding Algorithms

Abstract: Abstract. We outline here the next generation of cluster-finding algorithms. We show how advances

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2004
2004

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In order to compute accurate GCVFs down to the lowest possible circular velocities, we used the nearest clusters. Miller et al, 2002 (in prep) have identified 62 clusters in the Equatorial Stripes of the SDSS using the C4 algorithm (Nichol et al 2001;Gomez et al 2002). This algorithm uses the observed phenomenon that galaxies in clusters have similar colors as well as locations.…”
Section: Cluster Samplementioning
confidence: 99%
“…In order to compute accurate GCVFs down to the lowest possible circular velocities, we used the nearest clusters. Miller et al, 2002 (in prep) have identified 62 clusters in the Equatorial Stripes of the SDSS using the C4 algorithm (Nichol et al 2001;Gomez et al 2002). This algorithm uses the observed phenomenon that galaxies in clusters have similar colors as well as locations.…”
Section: Cluster Samplementioning
confidence: 99%